Electromagnetic turbulence in increased β plasmas in the Large Plasma Device. (9th August 2021) - Rossi, G.D.; Carter, T.A.; Seo, B.; Robertson, J.; Pueschel, M.J.; Terry, P.W.
Abstract : The variation of pressure-gradient-driven turbulence with plasma $β$ (up to $β ≈ 15\, %$ ) is investigated in linear, magnetized plasma. The magnitude of magnetic fluctuations is observed to increase substantially with increasing $β$ . More importantly, parallel magnetic fluctuations are observed to dominate at higher $β$ values, with $δ B_\parallel / δ B_\perp ≈ 2$ and $δ B / B_0 ≈ 1\, %$ . Parallel magnetic fluctuations are strongly correlated with density fluctuations and the two are observed to be out of phase. The relative magnitude of and cross-phase between density and parallel magnetic field fluctuations are consistent with the dynamic pressure balance ($P+{B_{0}^2}/{2μ _0} = constant$ ). A local slab model theory for electromagnetic, modified drift Alfvén waves, including parallel magnetic fluctuations, shows partial agreement with experimental observations.